Estudo de ganhos de produtividade e de qualidade em máquinas CNC com o uso de sistemas Toolsetter Laser - Costa, Francisco Soares da (2014)
In an increasingly competitive market, the growing quest for quality, flexibility and increased productivity, among others, is providing transformations that reflect in all areas of manufacturing. The advancement in technology follows this situation with new equipment and new products, and companies are encouraged to seek innovative methods of production that makes them more flexible and without loss of quality or increase in production costs. In the machining field, companies make use of techniques and resources that enable the reduction of losses in its production system for the optimization of time, reducing the consumption of materials and energy, and the production of parts with high quality levels, and among these actions are those related to reducing setup times. In this context, the present study aims to evaluate the gains in productivity and quality in CNC machines, with the use of toolsetter laser systems used during setup to perform sizing tools (Presetting). As a result of this study, it is concluded that it is possible to obtain better accuracy in measuring tools, as well as reducing downtime for setup, creating the effect of increasing productivity and quality dimensions of machined parts.